POTENSI OBJEK WISATA LUWENG COKRO KABUPATEN GUNUNG KIDUL DAERAH ISTIMEWA YOGYAKARTA SEBAGAI DESTINASI WISATA MINAT KHUSUS BERBASIS EKOWISATA - , FADHLAN TRIAKUSUMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
According to the authors , which is owned by the potential attraction Luweng Clark had barely meet the basic requirements of a tourist -based ecotourism . It is directly or indirectly a very menunjuang development as one of the attractions and potential tourist attraction that appeals to wisatawandan to increase tourist arrivals in the region Gunungkidul , especially Umbulrejo Village area . Based on the discussion in the previous chapters , it can be concluded as follows : Potential of the attraction Luweng Clark actually refers to the formation of basic provisions based ecotourism attraction . It can be seen from the management was taken over by the local people and the community around Attraction prefer to manage potential of their own territory . Including tourist areas and all commodities that exist around the object . People are still trying to take advantage of existing land used for private purposes and the carrying capacity of the existence of the attraction . Good move , but can not properly maximized by managers . People are still feeling - touch management and development steps to be performed on an ongoing basis later . Local authorities are still not paying full attention to the existence of this unique attraction . This certainly affects the limits development steps to be performed by the manager . Therefore , the manager always seek any form of help from the outside to keep the existence of this attraction . It is certainly not easy , because what is done by the manager of an independent step that rarely brings positive results . Basically , not all of the potential well is maximized by managers even though they already have an idea on sustainable management . This happens due to lack of funding in total . And again enthusiasts of attraction is mostly derived from certain interest groups.